Die ausländischen Ehregäste Hitlers gedenken am Ehrenmal Unter den Linden der Gefallenen des Weltkriegs
Die ausländischen Ehregäste Hitlers gedenken am Ehrenmal Unter den Linden der Gefallenen des Weltkriegs.